(3oYeOI GdcJGH GdLGeY dafhf GdBOGHs - (3LGQ Gddg oHNJjGQ GdQGRjs
(3ChdgG (B:s
(3GdMeO ddg GdPj CHQR ef ecfhfGJ CSQGQg cfhRG, hCMQR ef ObGFb UfYg dUahI Ndbg QehRG hHYO, aEf CMb eG fWb Hg dSGf, hCYQH Yfg HjGf, cJGH jSdjc s
(3BNQgG (B:s
(3hajeG CJjfG Hg caGjI def dg COfi OQGjI, hGdMeO ddg hMOg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B49 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs